Validating the factor structure of the drug free schools and communities scale for child welfare involved youth. Issue 1 (1st January 2022) - Cage, Jamie; Coles, D. Crystal; McGinnis, Hollee A.; Yoon, Susan; Pitts, Britney E.
ABSTRACT: The Drug Free Schools and Communities Act scale (DFSCA) has been widely used to measure school engagement in studies utilizing the National Survey of Child and Adolescent Well-Being (NSCAW) data. Recent analyses using NSCAW-I suggest that the best use of the DFSCA scale is a three-factor structure measuring emotional, behavioral, and cognitive-behavioral engagement. However, this three-factor structure presented concerns with the cognitive-behavioral engagement construct, warranting further analyses. This study aimed to test the three-factor structure in separate samples, and to test an alternative model that excluded the cognitive-behavioral engagement construct. Using NSCAW-II data, we performed a series of confirmatory factor analyses, to explore the fit of the hypothesized and alternative models across three random samples. We extracted three random samples from the NSCAW-II data, without replication. Each sub-sample represented 20 % of the larger NSCAW-II sample. The samples included children between the ages of 6 and 15 who were involved with the child welfare system due to a maltreatment report. Results indicated that both the three-factor structure that includes the cognitive-behavioral engagement construct, and the two-factor structure that excludes the factor fit the data well. Implications for using these factor structures in future research is discussed.